Bentuk dan Dampak Kekerasan Dalam Berpacaran: Perspektif Perbedaan Jenis Kelamin - Rini, Rini (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
The number of violence in relationship has been increasing, this increase is not only happening to women, but also to men so it is necessary needed to explore how forms of violence in relationship are experienced by men and women, as well as how the violence affects both men and women. Respondents of this study were 402 people who had experienced violence in relationship, either in the type of physical violence, psychological violence, economic violence, activity restriction violence, or sexual violence. By using Accidental Sampling technique a Google Forms was distributed via WhatsApp, Telegram, and email to collect data. Data analysis was carried out with a descriptive approach. The results of the analysis shows that women are most vulnerable to experience various types of violence in relationship. However, men are more likely to experience the effects of the violence itself than women.